Study of surfactant—liposome interactions at sublytic level by means of a surface probe. Issue 3 (2002) - Cócera Cócera, M. M.; López López, O. O.; Estelrich Estelrich, J. J.; Parra Parra, J. L. J. L.; de la Maza de la Maza, A. A.
Abstract : The incorporation of the sodium lauryl ether sulfate (SLES) on phosphatidylcholine (PC) liposomes has been studied with time using the fluorescent probe 2‒( p ‒toluidinyl)‒naphthalene‒6‒sodium sulfonate (TNS). This probe reports changes on the surface potential of PC liposomes by effect of the anionic surfactant adsorption. The addition of small SLES amounts promoted an abrupt fall in the fluorescence intensity (F.I.) and this fall was already detected 10 secs after mixing. Only slight changes with time were observed in the F.I. of SLES—liposome‒probe systems. These results indicate a fast and almost complete incorporation of SLES on the liposome surface. The surfactant/lipid molar ratios ( Re ) and the surfactant partition coefficients bilayer/aqueous phase ( K ) were determined from the linear dependence between lipid and surfactant concentrations obtained for a fixed number of surfactant molecules on the liposome surface. The Re values indicated that the highest SLES ability to adsorb on the surface occurs at the initial adsorption moments. The K values indicated that the affinity of the surfactant by the liposomes decreased after about 7500 surfactant molecules were adsorbed on the bilayer. This fact is probably caused by the increase of electrostatic repulsion between surfactant monomers in the bulk solution and the bound surfactant. The aforementioned linear dependence obtained from the data for a given number of SLES molecules on the bilayer and the range of SLES concentrations used (below/above its critical micelle concentration, CMC) suggest an adsorption mechanism regardless of the surfactant concentration: a monomeric adsorption of SLES is always assumed in both above/below surfactant CMC. In comparison with the higher adsorption reported for the analogous sodium dodecyl sulfate, the ethylene oxide moles in SLES could hinder its incorporation on PC liposomes. Thus, this study of sublytic interactions allows to follow the incorporation of surfactants on the lipid bilayers and to compare the effect of different surfactants on the membranes before the lysis.